PENGARUH BRAND IMAGE DAN KUALITAS PELAYANAN TERHADAP KEPUASAN WISATAWAN NUSANTARA KE BALI ZOO SINGAPADU, GIANYAR - Wrecika Vishnuputri, I Gusti Agung Ayu; Suardana, I Wayan; Wijaya, NMS. (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
The selection of the location of the tourist attraction that you want to visit is usually influenced by several aspects, including how the image of the tourist attraction itself is and the quality of service that will be provided at the tourist attraction, especially in pandemic conditions. As one of the tourist attractions affected by the pandemic, Bali Zoo maintains its image as a family-friendly tourist attraction and is safe to visit. In addition, Bali Zoo has also added new services that are needed at this time in accordance with standard operating procedures for tourist attractions during the pandemic. This study aims to determine the effect of brand image and service quality on the satisfaction of domestic tourists visiting Bali Zoo. The sample used is domestic tourists who visit Bali Zoo in 2020-2021.sampling technique used purposive sampling on 100 respondents. Sampling technique used was purposive sampling technique and used a Likert scale model questionnaire which was calibrated using the validity test and the reliability test was calculated using the Cronbach alpha using SPSS 22.0. The data analysis technique in this study used multiple linear regression analysis techniques. Based on the calculation of the IBM SPSS Statistics version 22.0 software, the results show that there is a significant influence between brand image and service quality variables on the satisfaction of domestic tourists visiting the Bali Zoo. This is evidenced from the analysis of the determination of the influence of brand image and service quality on the satisfaction of visiting domestic tourists, which is 71%. Furthermore, the influence of brand image and service quality on the satisfaction of visiting domestic tourists gets Fcount 118, 887 > Ftable 3.939, this means that the variable brand image and service quality has a positive effect on the satisfaction of domestic tourists visiting Bali Zoo.